Who are the workers who never joined a union? Empirical evidence from Germany - Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2005)
Using representative data from the German social survey ALLBUS 2002 and the European Social Survey 2002/03, this paper provides the first empirical analysis of trade union never-membership in Germany. We show that between 54 and 59 percent of all employees in Germany have never been members of a trade union. Individuals' probability of never-membership is significantly affected by their personal characteristics (in particular age, education and status at work), their political orientation and (to a lesser degree) their family background, and by broad location. In addition, occupational and workplace characteristics play a significant role. Most important in this regard is the presence of a union at the workplace.
Keywords: J51; 330; union membership; never-membership; Germany; Gewerkschaft; Mitgliedschaft; Gewerkschaftlicher Organisationsgrad; Deutschland